The role of defaultness and personality factors in sarcasm interpretation: evidence from eye-tracking during reading - Filik, Ruth; Howman, Hannah; Ralph-Nearman, Christina; Giora, Rachel (Taylor & Francis, 2018)
Theorists have debated whether our ability to understand sarcasm is principally determined by the context (Gibbs, 1994; Utsumi, 2000) or by properties of the comment itself (Giora, 1997; 2003; Grice, 1975). The current research investigated an alternative view which broadens the focus on the comment itself, suggesting that mitigating a highly positive concept by using negation generates sarcastic interpretations by default (Giora et al., 2015a, 2018). In the current study, pre-tests performed on the target utterances presented in isolation established their default interpretations; novel affirmative phrases (e.g., He is the best lawyer) were interpreted literally, whereas equally novel negative counterparts (e.g., He isn’t the best lawyer) were interpreted sarcastically. In Experiment 1 (an eye-tracking study), prior context biased these utterances towards literal or sarcastic interpretations. Results showed that target utterances were easier to process in contexts supporting their default interpretations, regardless of affirmation/negation. Results from a second eye-tracking experiment suggested that readers’ tendency to interpret negative phrases sarcastically is related to their own tendency to use malicious humor. Our findings suggest that negation leads to certain ambiguous utterances receiving sarcastic interpretations by default and that this process may be further intensified by personality factors.